Odpowiedź :
A) x+(3x-Y kwadrat +7) = x + 3x - y² + 7 = 4x - y² +7
b) -a+(2a-3b-1) = -a + 2a - 3b - 1 = a - 3b - 1
c) -b sześcianu -(b sześcian-b kwadrat -b) = -b³ - b³ + b² + b = -2b³ + b² + b
d) (2a-3b)+(4a -b) = 2a - 3b + 4a - b = 6a - 4b
e) -(x kwadrat -3x)+(x kwadrat+3x) = -x² + 3x + x² + 3x = 6x
f)(a+b-c)-(2a-b+2c) = a + b - c - 2a + b - 2c = -a + 2b - 3c
A) x+(3x-Y kwadrat +7) = x + 3x - y² + 7 = 4x - y² +7
b) -a+(2a-3b-1) = a - 3b - 1
c) -b sześcianu -(b sześcian-b kwadrat -b) = -2b³ + b² + b
d) (2a-3b)+(4a -b) = 6a - 4b
e) -(x kwadrat -3x)+(x kwadrat+3x) = -x² + 3x + x² + 3x = 6x
f)(a+b-c)-(2a-b+2c) = -a + 2b - 3c